PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL DAN PERGANTIAN CHIEF EXECUTIVE OFFICER (CEO) TERHADAP RETURN SAHAM - Sevilla Elfa Huwaida; Amalia Ilmiani (Jurnal Akuntansi dan Pajak, 2024)
Stock return is the percentage of profits obtained from investments that have been made, which is often an attractive factor for investors to invest their capital in the stock market. This is a basic framework that writers can use to illustrate the concept. shares are the rate of return on the investment that has been made. Stock returns can attract investors to invest their funds in the capital market. This research aims to determine the effect of financial performance as proxied by liquidity and profitability, capital structure and CEO turnover on stock returns in energy sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample for this research was 84 data with a sampling method, namely purposive sampling. The analysis technique used is PLS-SEM using WarpPLS 7.0 software. The results of this research show that (1) Liquidity (CR) has no effect on stock returns, (2) Profitability (ROE) has a significant positive effect on stock returns, (3) Capital structure (WCTO) has a significant negative effect on stock returns, (4) CEO change has no effect on stock returns.